First report of Sneathia sanguinegens together with Mycoplasma hominis in postpartum prosthetic valve infective endocarditis: a case report - Kotaskova, Iva; Nemec, Petr; Vanerkova, Martina; Malisova, Barbora; Tejkalova, Renata; Orban, Marek; Zampachova, Vita; Freiberger, Tomas (BMC infectious diseases, 2017)
BACKGROUND: The presence of more than one bacterial agent is relatively rare in infective endocarditis, although more common in prosthetic cases. Molecular diagnosis from a removed heart tissue is considered a quick and effective way to diagnose fastidious or intracellular agents. CASE PRESENTATION: Here we describe the case of postpartum polymicrobial prosthetic valve endocarditis in a young woman. Sneathia sanguinegens and Mycoplasma hominis were simultaneously detected from the heart valve sample using broad range 16S rRNA polymerase chain reaction (PCR) followed by sequencing while culture remained negative. Results were confirmed by independent PCR combined with denaturing gradient gel electrophoresis. Before the final agent identification, the highly non-compliant patient left from the hospital against medical advice on empirical intravenous treatment with aminopenicillins, clavulanate and gentamicin switched to oral amoxycillin and clavulanate. Four months after surgery, no signs of inflammation were present despite new regurgitation and valve leaflet flail was detected. However, after another 5 months the patient died from sepsis and recurrent infective endocarditis of unclarified etiology. CONCLUSIONS: Mycoplasma hominis is a rare causative agent of infective endocarditis. To the best of our knowledge, presented case is the first report of Sneathia sanguinegens detected in this condition. Molecular techniques were shown to be useful even in polymicrobial infective endocarditis samples.
Keywords: mykoplazmové infekce; Fusobacteriaceae Infections; RNA, Ribosomal, 16S; poporodní období; Anti-Bacterial Agents; Amoxicillin; těhotenství; bakteriální endokarditida; Mycoplasma Infections; Postpartum Period; Infective endocarditis; mužské pohlaví; Leptotrichia; Adult; Heart Valve Prosthesis; Postpartum endocarditis; Polymicrobial infections; infekce bakteriemi čeledi Fusobacteriaceae; Mycoplasma hominis; Endocarditis, Bacterial; ženské pohlaví; RNA ribozomální 16S; Humans; amoxicilin; Pregnancy; infekce spojené s protézou; Mycoplasma; srdeční chlopně umělé; antibakteriální látky; Sneathia; Prosthesis-Related Infections; dospělí; Female; lidé; Male